2018
DOI: 10.1039/c7fo01715d
|View full text |Cite
|
Sign up to set email alerts
|

Black pepper-based beverage induced appetite-suppressing effects without altering postprandial glycaemia, gut and thyroid hormones or gastrointestinal well-being: a randomized crossover study in healthy subjects

Abstract: Pleiotropic effects of spices on health, particularly on glucose metabolism and energy regulation, deserve further clinical investigation into their efficacy. The aim of the current study was to evaluate whether consumption of a black pepper-based beverage (BPB) preload containing 20 mg gallic acid equivalent (GAE) would exert any effect on postprandial glycaemia, appetite sensations, gut hormones, thyroid function, and gastrointestinal well-being after a white wheat bread (WWB) challenge meal containing 50 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…Although gut hormones are altered postprandially with a proven role in the digestion, absorption, and subsequent metabolic fate of nutrients, their physiological role in the regulation of eating behavior is still not fully understood [25]. Indeed, we recently showed that a black-pepper-based beverage can modulate overall appetite sensations without altering gut hormones (PYY and GLP-1) release [4]. In that report, it was speculated that other putative pathways such as activation of transient receptor potential (TRP) cation channels, which was previously shown to be activated by pungent spices such as cinnamon [26], might be involved in the modulation of appetite sensations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gut hormones are altered postprandially with a proven role in the digestion, absorption, and subsequent metabolic fate of nutrients, their physiological role in the regulation of eating behavior is still not fully understood [25]. Indeed, we recently showed that a black-pepper-based beverage can modulate overall appetite sensations without altering gut hormones (PYY and GLP-1) release [4]. In that report, it was speculated that other putative pathways such as activation of transient receptor potential (TRP) cation channels, which was previously shown to be activated by pungent spices such as cinnamon [26], might be involved in the modulation of appetite sensations.…”
Section: Resultsmentioning
confidence: 99%
“…Several nutrients and food groups, including plants, which are rich in diverse bioactive compounds have received great attention as potential modulators of appetite [1,2]. However, little is known with regards to the impact of spices such as turmeric [3], black pepper [4], cinnamon [3,5,6,7], and ginger [8] on the regulation of appetite and appetite-related hormones such as peptide tyrosine–tyrosine (PYY), glucagon-like peptide 1 (GLP-1), and cholecystokinin (CCK). The release of PYY and GLP-1 induced by meals is known to be associated with the appetite suppression and delayed gastric emptying, among others.…”
Section: Introductionmentioning
confidence: 99%
“…4 was tentatively assigned as di-hydroxybenzoic acid hexoside-pentoside. This compound has previously been described in plants [24]. With regard to caffeic acid derivatives, two isomers were proposed.…”
Section: Resultsmentioning
confidence: 99%
“…Black pepper, cinnamon, ginger, horseradish and saffron have all been investigated for their appetitive effects based on one or more of the mechanisms listed above. However, the findings are mixed and thus far from definitive …”
Section: Culinary Herbs and Spicesmentioning
confidence: 97%
“…However, the findings are mixed and thus far from definitive. 24,31,34,35 Another CHS, which has been the focus of this area of research, is red chilli pepper, because of its constituent capsaicin. Capsaicin is responsible primarily for the pungent aroma and taste of this CHS, and, via the activation of the central nervous system located 'capsaicin receptor', is reported to increase lipid oxidation and decrease adipose tissue.…”
Section: Effect On Appetitementioning
confidence: 99%